The existence of arbitration verdict cancellation efforts regarding final and binding characteristics - Camelia, Noer Dini; Lutfiadi, Lutfiadi; Heryanti, Febrina; Wardani, Win Yuli; Purwandi, Agustri (IHSA Institute, 2024)
The arbitration verdict must include a verdict implementation period. It is based on the arbitration verdict characteristics based on Article 60 AADR LAW (Law on Arbitration and Alternative Dispute Resolution), namely that an arbitration verdict is final, has permanent legal force, and is binding on both parties; therefore, the legal consequences do not only apply to the parties who are arbiter but also arbitration verdicts cannot be further tested for legal consequences by other institutions. However, the provisions of Article 60 AADR LAW are followed by the provisions of Article 70 AADR LAW, which allows for arbitration verdict cancellation by the District Court as in Article 71 AADR LAW. Hence, this research aims to determine the binding power of an arbitration verdict and the District Court’s authority in canceling an arbitration verdict. The research methodology was normative research with statutory and conceptual approaches. The research results stated that efforts to cancel the arbitration verdict by the District Court had implications for the loss of the final and binding characteristics of the arbitration verdict. Efforts to cancel the arbitration verdict required to reconsider its existence